Hiding Text within LSB of Image Pixels - Jain, Rupali (Innovare Journal of Engineering and Technology, 2015)
Data security is maintained by assuming the consistency and accuracy of data over its entire life cycle. Security aspects come into play when it is necessary or desirable to protect the information transmission from an opponent who may present a threat to confidentiality, authenticity, data integrity and denial of service. Here, we are proposing a separable reversible data hiding technique in which data to be hidden is text. This technique proposed a way how to hide large amount of text behind an image. Process involves creating space after compressing least significant bits of the image. Later, the data is hidden in this space.